2022
DOI: 10.1186/s41235-022-00430-5
|View full text |Cite
|
Sign up to set email alerts
|

Face masks impair facial emotion recognition and induce specific emotion confusions

Abstract: Face masks are now worn frequently to reduce the spreading of the SARS-CoV-2 virus. Their health benefits are undisputable, but covering the lower half of one's face also makes it harder for others to recognize facial expressions of emotions. Three experiments were conducted to determine how strongly the recognition of different facial expressions is impaired by masks, and which emotions are confused with each other. In each experiment, participants had to recognize facial expressions of happiness, sadness, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 45 publications
6
33
0
1
Order By: Relevance
“…Several studies have also observed a significant effect of facemasks on sadness expressed at 100% of intensity (Grenville & Dwyer, 2022;Maiorana et al, 2022). This drop in performance with the mask in our results can be explained by many confusions of sadness, at all intensities (low as high), with other emotions, such as disgust (see, for similar results, Carbon, 2020;Carbon et al, 2022;Kim et al, 2022;Rinck et al, 2022), fear (see also, Carbon et al, 2022;Rinck et al, 2022), and also neutral expression (see also Carbon, 2020;Carbon et al, 2022;Kim et al, 2022;Rinck et al, 2022).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Several studies have also observed a significant effect of facemasks on sadness expressed at 100% of intensity (Grenville & Dwyer, 2022;Maiorana et al, 2022). This drop in performance with the mask in our results can be explained by many confusions of sadness, at all intensities (low as high), with other emotions, such as disgust (see, for similar results, Carbon, 2020;Carbon et al, 2022;Kim et al, 2022;Rinck et al, 2022), fear (see also, Carbon et al, 2022;Rinck et al, 2022), and also neutral expression (see also Carbon, 2020;Carbon et al, 2022;Kim et al, 2022;Rinck et al, 2022).…”
Section: Discussionsupporting
confidence: 82%
“…This impact was the source of many confusions of this expression exclusively with neutral. In other studies, happiness was often confused with surprise (Verroca et al, 2022) and also with neutral (Carbon, 2020;Carbon et al, 2022;Rinck et al, 2022). These difficulties in recognizing happiness with the mask could be due to the occlusion of the mouth region, which plays an important role in the recognition of this expression (Wegrzyn et al, 2017).…”
Section: Discussionmentioning
confidence: 88%
“…Grenville and Dwyer ( 2022 ) found that there was an overall emotion recognition accuracy for faces shown without masks compared to when shown wearing them, but this effect varied by emotion (advantage without masks in disgust, happiness, and sadness; no effect for neutral; lower accuracy without masks for anger and fear). Using a similar static-based face emotion recognition task, Rinke et al ( 2022 ) showed that the impairment was largest for disgust, followed by fear, surprise, sadness, and happiness. It was not significant for anger (also see Wong & Estudillo, 2022 ) or neutral expressions.…”
mentioning
confidence: 99%
“…During the implementation and clinical trials, the influence of wearing a mask was not considered or tested in this work. Wearing a mask will cover the lower part of the face and make most facial features invisible, which will decrease the facial expression recognition accuracy [ 41 , 42 ]. Third, for the teleoperation system, this work was based on unilateral teleoperation and we did not investigate the force feedback from the robot to the operator.…”
Section: Discussionmentioning
confidence: 99%